Negative enthalpy duplex stainless steel material with high strength, high plasticity and high corrosion resistance and preparation method

CN119824341AActive Publication Date: 2025-04-15SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411939403.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-15
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

[0006]鉴于上述现有技术的不足,本发明的目的在于提供一种兼具高强度、高塑性与高耐蚀性的负焓双相不锈钢材料及制备方法,旨在解决开发具有更高强度、塑性和耐蚀性的新型不钢材以满足更为严苛的服役环境的问题

Benefits of technology

[0022] The present invention provides a Fe a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j The series of negative enthalpy duplex stainless steel materials are composed of iron, chromium, nickel, molybdenum, manganese, carbon, silicon, titanium, aluminum and vanadium according to the above ratios and are made by a vacuum arc melting furnace. The series of negative enthalpy duplex stainless steel materials contain ferrite (α, body-center cubic structure (BCC)) and austenite (γ, face-center cubic structure (FCC)) in structure, and the microstructure structure and mechanical properties of the alloy can be adjusted by adjusting the proportions of different metal elements. This series of negative enthalpy duplex stainless steel materials exhibits high strength and high plastic mechanical properties. Meanwhile, negative enthalpy duplex stainless steel material exhibits excellent corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824341A_ABST
    Figure CN119824341A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal materials, in particular to a negative enthalpy duplex stainless steel material with high strength, high plasticity and high corrosion resistance and a preparation method. The negative enthalpy duplex stainless steel material is Fe Cr N < c > Mo < d > Mn < e > C < f > Si < g > Ti < h > Al V < j >; wherein a, b, c, d, e, f, g, h, i and j respectively correspond to the mass percentage of each element, a is equal to 60-70 wt%, b is equal to 15-20 wt%, c is equal to 10-15 wt%, d is equal to 0-5 wt%, e is equal to 1-5 wt%, f is equal to 0.015 wt%, g is equal to 0-1 wt%, h is equal to 0-3 wt%, i is equal to 0-0.5 wt%, and d, g, h, i and j are all not equal to 0. The series of negative enthalpy duplex stainless steel materials structurally contain ferrite and austenite, and the microscopic structure and the mechanical property of the alloy can be regulated and controlled by adjusting the proportion of different metal elements. The series of negative enthalpy duplex stainless steel materials show high-strength and high-plasticity mechanical properties. Meanwhile, the negative enthalpy duplex stainless steel material shows excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to a negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance and a preparation method thereof. Background Art

[0002] Metal structural materials are the foundation of marine engineering materials and are widely used in warships, carrier-based aircraft, manned / unmanned submersibles, offshore wind power plants, marine ships, offshore platforms and marine buildings. Faced with extreme service environments such as high temperature, high humidity, and high salt in the ocean, as well as complex stress loads such as seawater tidal fluctuations and wind and waves, metal materials are required to have excellent mechanical properties, such as high strength, high toughness, corrosion resistance and wear resistance. Traditional stainless steel and low alloy steel (such as typical E690, Q355, and 304, 316L stainless steel, etc.) have good toughness and corrosion resistance. However, their yield strength is usually low, only ~300MPa, which is difficult to meet the material strength requirements of advanced high-end equipment. Secondly, high-strength alloy steels, such as medium duplex steels and medium Mn steels, are prone to corrosion in extreme marine environments, resulting in catastrophic damage to the material in the early stage, and are difficult to serve for a long time. Therefore, the development of new marine steel materials with both high strength and toughness and corrosion resistance has become the biggest challenge faced by marine engineering materials in the service process.

[0003] Traditional steel chemical composition design concepts are often based on empirical methods and rules. For example, adding chromium (Cr) and molybdenum (Mo) elements can increase the corrosion resistance of steel, increase the proportion of ferrite in steel, and thus increase the yield strength of steel. Nickel (Ni) elements can stabilize the austenite phase, thereby controlling the volume fraction of austenite to adjust the dual-phase ratio and promote the improvement of steel toughness. Refractory metal elements such as niobium (Nb) and tantalum (Ta) play a role in solid solution strengthening and improve the strength of steel.

[0004] However, with the rapid development of modern science and technology and industry, it is urgent to develop new steels with higher strength, plasticity and corrosion resistance to meet more stringent service environments. This poses a major challenge to the design and preparation of alloy chemical composition.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a negative enthalpy duplex stainless steel material and a preparation method having high strength, high plasticity and high corrosion resistance, aiming to solve the problem of developing a new type of stainless steel with higher strength, plasticity and corrosion resistance to meet more stringent service environments.

[0007] The technical solution of the present invention is as follows:

[0008] In a first aspect of the present invention, a negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance is provided, wherein the negative enthalpy duplex stainless steel material is Fe a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j ;

[0009] Wherein: a, b, c, d, e, f, g, h, i and j correspond to the mass percentage ratio of each element, a = 60-70wt%, b = 15-20wt%, c = 10-15wt%, d = 0-5wt%, e = 1-5wt%, f = 0.015wt%, g = 0-1wt%, h = 0-3wt%, i = 0-0.5wt%, j = 0-0.5wt%, d, g, h, i and j are not 0;

[0010] The negative enthalpy duplex stainless steel material contains ferrite and austenite in structure.

[0011] Optionally, the negative enthalpy duplex stainless steel material is Fe a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j ;

[0012] Wherein: a, b, c, d, e, f, g, h, i and j correspond to the mass percentage ratio of each element, a=62-65wt%, b=16-18wt%, c=12-14wt%, d=2-4wt%, e=1.5-2.5wt%, f=0.015wt%, g=0.45-0.55wt%, h=0.5-3wt%, i=0.1-0.5wt%, j=0.03-0.2wt%.

[0013] Optionally, the negative enthalpy duplex stainless steel is Fe 64.2 Cr 16.6 Ni 12.8 Mo 3.2 Mn 1.8 C 0.015 Si 0.5 Ti 0.7 Al 0.1 6V 0.03 , Fe63.6 Cr 16.5 Ni 12.7 Mo 3.1 Mn 1.8 C 0.015 Si 0.5 Ti 1.4 Al 0.23 V 0.06 , Fe 63.1 Cr 16.3 Ni 12.7 Mo 3.1 Mn 1.7 8C 0.015 Si 0.5 Ti 2.1 Al 0.3 V 0.1 , Fe 62.5 Cr 16.2 Ni 12.5 Mo 3.1 Mn 1.76 C 0.015 Si 0.5 Ti 2.8 Al 0.36 V 0.13 and Fe 62 Cr 16 Ni 12.5 Mo3Mn 1.75 C 0.015 Si 0.5 Ti 3.5 Al 0.4 V 0.16 One of them.

[0014] Optionally, the purity of each element in the negative enthalpy duplex stainless steel material is Fe≥99.95%, Cr≥99.95%, Ni≥99.95%, Mo≥99.99%, Mn≥99.8%, C≥99.99%, Si≥99.99%, Ti≥99.99%, Al≥99.99% and V≥99.95%.

[0015] The second aspect of the present invention provides a method for preparing the negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance according to the present invention, wherein the method comprises the following steps: placing each raw material into an arc melting furnace according to the component ratio, striking an arc to melt the raw material in an inert atmosphere environment, and obtaining the negative enthalpy duplex stainless steel material.

[0016] Optionally, the preparation method specifically includes the following steps: first, ultrasonically cleaning each raw material, and then placing the cleaned raw materials in a water-cooled copper crucible in an arc melting furnace in order of melting point from low to high according to the component ratio, placing sponge titanium in the middle crucible of the water-cooled copper crucible, and striking an arc to melt the raw materials in an inert atmosphere until they are fully miscible to obtain the negative enthalpy duplex stainless steel material.

[0017] Optionally, the inert atmosphere environment is a vacuum oxygen-free environment, which is obtained by the following operations: evacuating the arc melting furnace to a vacuum degree of <4 Pa using a mechanical pump, and then evacuating the furnace to a vacuum degree of <4×10 -4 Pa, and then introduce argon gas with a purity of 99.99% to 0.08Mpa; repeat the above process twice, and finally fill the argon gas to 0.06Mpa, and then arc melt the sponge titanium twice to absorb residual oxygen.

[0018] Optionally, in the step of arc-melting the raw material in an inert atmosphere environment, the number of arc-melting of the raw material is greater than 4 times, and after each arc-melting, the arc-melted material in the water-cooled copper crucible is turned over before the next arc-melting, and the sponge titanium is arc-melted before the next arc-melting.

[0019] Optionally, the time of each arc melting is 1.0-2.0 min, and in addition to the first arc melting and the last arc melting, the arc melting of the raw materials also includes magnetic stirring of the raw materials.

[0020] Optionally, the voltage of each arc melting is 10-15V, and the current of each arc melting is 300-350A.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] The present invention provides a Fe a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V jA series of negative enthalpy duplex stainless steel materials are composed of iron, chromium, nickel, molybdenum, manganese, carbon, silicon, titanium, aluminum and vanadium in the above proportions and are made by vacuum arc melting furnace. The structure of this series of negative enthalpy duplex stainless steel materials contains ferrite (α, body-centered cubic structure (BCC)) and austenite (γ, face-centered cubic structure (FCC)), and the alloy microstructure and mechanical properties can be regulated by adjusting the proportion of different metal elements. This series of negative enthalpy duplex stainless steel materials exhibits high strength and high plasticity mechanical properties. At the same time, negative enthalpy duplex stainless steel materials exhibit excellent corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The Fe prepared in Examples 1-5 of the present invention a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j X-ray diffraction patterns of a series of negative enthalpy duplex stainless steel materials;

[0024] Figure 2 The Fe prepared in Examples 1-5 of the present invention a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j Room temperature tensile stress-strain curves of a series of negative enthalpy duplex stainless steel materials;

[0025] Figure 3 The Fe prepared in Examples 1-4 of the present invention a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j Polarization curves of a series of negative enthalpy duplex stainless steel materials in 3.5wt.% NaCl. DETAILED DESCRIPTION

[0026] The present invention provides a negative enthalpy duplex stainless steel material and a preparation method thereof with high strength, high plasticity and high corrosion resistance. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] The embodiment of the present invention provides a negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance, wherein the negative enthalpy duplex stainless steel material is Fe a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j ;

[0028] Wherein: a, b, c, d, e, f, g, h, i and j correspond to the mass percentage ratio of each element, a = 60-70wt%, b = 15-20wt%, c = 10-15wt%, d = 0-5wt%, e = 1-5wt%, f = 0.015wt%, g = 0-1wt%, h = 0-3wt%, i = 0-0.5wt%, j = 0-0.5wt%, d, g, h, i and j are not 0;

[0029] The negative enthalpy duplex stainless steel material contains ferrite and austenite in structure, and further the volume fraction of austenite is between 50% and 90%.

[0030] The series of negative enthalpy duplex stainless steel materials provided in the embodiment of the present invention are composed of iron, chromium, nickel, molybdenum, manganese, carbon, silicon, titanium, aluminum and vanadium according to the above-mentioned proportions. The series of negative enthalpy duplex stainless steel materials contain ferrite (BCC) and austenite (FCC) in structure, and the alloy microstructure and mechanical properties can be regulated by adjusting the proportion of different metal elements. The series of negative enthalpy duplex stainless steel materials exhibit high strength and high plasticity mechanical properties. At the same time, the negative enthalpy duplex stainless steel material exhibits excellent corrosion resistance. Therefore, the series of negative enthalpy duplex stainless steel materials show great application potential, for example, in marine ships, marine engineering platforms, nuclear power plants, chemical plants, etc., it has great application potential.

[0031] Compared with the traditional 304 and 316 stainless steels, the negative enthalpy duplex stainless steel material composition of the present invention is characterized by the addition of Al, Ti and V alloy elements. This is because iron has a relatively negative mixing enthalpy (ΔH mix ), where ΔH mix(Fe-Al) = -11 kJ / mol, ΔH mix (Fe-Ti) = -17 kJ / mol, ΔH mix (Fe-V) = -7 kJ / mol. Therefore, by adding negative enthalpy elements (Al, Ti and V), it is expected to produce chemical affinity differences between elements in the ideal entropy solid solution, thereby forming localized negative enthalpy chemical affinity cluster heterogeneous structures, such as composition fluctuations, local order, etc. These nano-heterogeneous interfaces can not only effectively pin dislocation movement and promote its movement and proliferation in the form of multi-system slip and cross slip, but also serve as intracrystalline dislocation sources to produce ultra-high density dislocations, thereby significantly improving the work hardening ability of stainless steel, and then achieving the synergistic effect of ultra-high yield strength and large tensile plasticity.

[0032] In addition, by adjusting the range of h, i and j, the mixing enthalpy of the alloy can be adjusted (-9kJ / mol to -4kJ / mol), thereby achieving high strength and high corrosion resistance.

[0033] In a preferred embodiment, the negative enthalpy duplex stainless steel material is Fe a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j ;

[0034] Wherein: a, b, c, d, e, f, g, h, i and j correspond to the mass percentage ratio of each element, a=62-65wt%, b=16-18wt%, c=12-14wt%, d=2-4wt%, e=1.5-2.5wt%, f=0.015wt%, g=0.45-0.55wt%, h=0.5-3wt%, i=0.1-0.5wt%, j=0.03-0.2wt%.

[0035] Under the above ratio, the series of negative enthalpy duplex stainless steel materials show excellent synergistic effects of strength, plasticity and corrosion resistance.

[0036] As an example, the negative enthalpy duplex stainless steel is Fe 64.2 Cr 16.6 Ni 12.8 Mo 3.2 Mn 1.8 C 0.015 Si 0.5 Ti 0.7 Al 0.1 6V 0.03 , Fe63.6 Cr 16.5 Ni 12.7 Mo 3.1 Mn 1.8 C 0.015 Si 0.5 Ti 1.4 Al 0.23 V 0.06 , Fe 63.1 Cr 16.3 Ni 12.7 Mo 3.1 Mn 1.7 8C 0.015 Si 0.5 Ti 2.1 Al 0.3 V 0.1 , Fe 62.5 Cr 16.2 Ni 12.5 Mo 3.1 Mn 1.76 C 0.015 Si 0.5 Ti 2.8 Al 0.36 V 0.13 and Fe 62 Cr 16 Ni 12.5 Mo3Mn 1.75 C 0.015 Si 0.5 Ti 3.5 Al 0.4 V 0.16 One of them.

[0037] The Fe provided in the embodiment of the present invention a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j The series of negative enthalpy duplex stainless steel materials have both high strength and high plasticity in terms of mechanical properties. 64.2 Cr 16.6 Ni 12.8 Mo 3.2 Mn 1.8 C 0.015 Si 0.5 Ti 0.7 Al 0.16 V 0.03The room temperature tensile yield strength is 400MPa, the tensile strength is 580MPa, the uniform elongation is 26%, and the pitting point in 3.5wt% NaCl aqueous solution is 0.24V; Fe 63.6 Cr 16.5 Ni 12.7 Mo 3.1 Mn 1.8 C 0.015 Si 0.5 Ti 1.4 Al 0.23 V 0.06 The room temperature tensile yield strength is 440MPa, the tensile strength is 670MPa, the uniform elongation is 27%, and the pitting point in 3.5wt% NaCl aqueous solution is 0.45V; Fe 63.1 Cr 16.3 Ni 12.7 Mo 3.1 Mn 1.78 C 0.015 Si 0.5 Ti 2.1 Al 0.3 V 0.1 The room temperature tensile yield strength is 643MPa, the tensile strength is 925MPa, the uniform elongation is 25%, and the pitting point in 3.5wt% NaCl aqueous solution is 0.47V; Fe 62.5 Cr 16.2 Ni 12.5 Mo 3.1 Mn 1.76 C 0.015 Si 0.5 Ti 2.8 Al 0.36 V 0.13 The room temperature tensile yield strength is 870MPa, the tensile strength is 1070MPa, the uniform elongation is 11.5%, and the pitting point in 3.5wt% NaCl aqueous solution is 0.49V; Fe 62 Cr 16 Ni 12.5 Mo3Mn 1.75 C 0.01 5Si 0.5 Ti 3.5 Al 0.4 V 0.16 The yield strength is 950MPa, the tensile strength is 1150MPa, and the uniform elongation is 3.5%.

[0038] In one embodiment, the purity of each element in the negative enthalpy duplex stainless steel material is Fe≥99.95%, Cr≥99.95%, Ni≥99.95%, Mo≥99.99%, Mn≥99.8%, C≥99.99%, Si≥99.99%, Ti≥99.99%, Al≥99.99% and V≥99.95%.

[0039] The embodiment of the present invention provides a method for preparing a negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance, wherein the negative enthalpy duplex stainless steel material is Fe a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j , wherein a=60-70wt%, b=15-20wt%, c=10-15wt%, d=0-5wt%, e=1-5wt%, f=0.015wt%, g=0-1wt%, h=0-3wt%, i=0-0.5wt%, j=0-0.5wt%, d, g, h, i and j are not 0;

[0040] The preparation method comprises the following steps: placing raw materials into an arc melting furnace according to the component ratio, striking an arc to melt the raw materials in an inert atmosphere to obtain the negative enthalpy duplex stainless steel material.

[0041] The negative enthalpy duplex stainless steel material provided in the embodiment of the present invention contains ferrite (BCC) and austenite (FCC) in structure, and the alloy microstructure and mechanical properties can be regulated by adjusting the ratio of different metal elements. The negative enthalpy duplex stainless steel material exhibits high strength and high plasticity mechanical properties. At the same time, the negative enthalpy duplex stainless steel material exhibits excellent corrosion resistance. Therefore, this series of negative enthalpy duplex stainless steel materials show great application potential, for example, in marine ships, marine engineering platforms, nuclear power plants, chemical plants, etc.

[0042] In one embodiment, the preparation method of the negative enthalpy duplex stainless steel material specifically includes the following steps: first, ultrasonically clean each raw material with anhydrous ethanol; secondly, to ensure that each element is fully melted, the cleaned raw materials are placed in a water-cooled copper crucible in an arc melting furnace in order of melting point from low to high according to the component ratio, the non-metallic raw materials are placed at the bottom of the copper crucible, and then placed in order from low to high according to the melting point of the metal, sponge titanium is placed in the middle crucible of the water-cooled copper crucible, and the raw materials are arc-melted in an inert atmosphere environment (such as an argon atmosphere environment) until they are fully miscible to obtain the negative enthalpy duplex stainless steel material.

[0043] The inert atmosphere environment can be a high vacuum oxygen-free environment, which is firstly subjected to multiple cycles of vacuuming and argon filling, and then the sponge titanium is melted to absorb residual oxygen before melting the raw materials.

[0044] The process of vacuuming-filling with argon-melting titanium sponge to absorb oxygen is specifically as follows: the arc melting furnace is vacuumed to a vacuum degree of <4 Pa by a mechanical pump, and then vacuumed to a vacuum degree of <4×10 -4 Pa, and then introduce argon gas with a purity of 99.99% to 0.08Mpa. Repeat the above process twice, and finally fill the argon gas to 0.06Mpa, then start arc melting of sponge titanium twice to absorb residual oxygen.

[0045] During the smelting process, the arc melting of the raw material is performed for more than 4 times, and after each arc melting, the arc melting material in the water-cooled copper crucible is turned over before the next arc melting. Before the next arc melting of the alloy, the titanium sponge is arc melted to absorb oxygen.

[0046] The time of each arc melting is 1.0-2.0min, and in addition to the first arc melting and the last arc melting, the arc melting of the raw materials also includes magnetic stirring of the raw materials.

[0047] The voltage of each arc melting is 10-15V, and the current of each arc melting is 300-350A.

[0048] The present invention is further described in detail below through several specific embodiments.

[0049] Example 1

[0050] This embodiment provides a Fe 64.2 Cr 16.6 Ni 12.8 Mo 3.2 Mn 1.8 C 0.015 Si 0.5 Ti 0.7 Al 0.16 V 0.03 Negative enthalpy duplex stainless steel material and preparation method thereof, the preparation method specifically comprises the following steps:

[0051] S1. Wash ten kinds of high-purity raw material particles (Fe, Cr, Ni, Mo, Mn, C, Si, Al, Ti and V) in an ultrasonic bath twice, then weigh them accurately according to the component ratio, and put them into a water-cooled copper crucible in order from low to high melting points, with the element with the lowest melting point placed at the bottom layer and the element with the highest melting point placed at the top layer. At the same time, put titanium sponge in the middle copper mold position;

[0052] S2. Close the door of the arc melting furnace, turn on the circulating water, turn on the mechanical pump, and evacuate. When the vacuum degree is lower than 4 Pa, turn on the molecular pump for further evacuation. When the vacuum degree is lower than 4×10 -4 When the pressure reaches 0.05 MPa, high-purity argon gas (pressure is about 0.08 MPa) is introduced; after repeating the above process twice, the argon gas is filled to 0.06 MPa in the last step.

[0053] S3, striking an arc in a high-purity argon atmosphere, melting the titanium sponge twice, and absorbing the residual oxygen in the furnace;

[0054] S4. First, high current smelting (smelting voltage 12V, melting current 330A) is used to melt all the raw material particles and mix them evenly. After the alloy button casting is cooled, it is turned over by a robot and smelted in the same way. Magnetic stirring is turned on during each smelting process after the second time. After each smelting, the alloy button casting needs to be turned over 180 degrees. A total of 4 smeltings are performed to make the alloy composition more uniform. The magnetic stirring is turned off during the last smelting to make it a smooth ingot, and suction casting is performed.

[0055] S5. After the alloy button ingot is completely cooled, open the furnace door and take out the sample.

[0056] Example 2

[0057] This embodiment provides a Fe 63.6 Cr 16.5 Ni 12.7 Mo 3.1 Mn 1.8 C 0.015 Si 0.5 Ti 1.4 Al 0.23 V 0.06 The preparation method of the negative enthalpy duplex stainless steel material is basically the same as that of Example 1, and the only difference is the component ratio.

[0058] Example 3

[0059] This embodiment provides a Fe 63.1 Cr 16.3 Ni 12.7 Mo 3.1 Mn 1.78 C 0.015 Si 0.5 Ti 2.1 Al 0.3 V 0.1 The preparation method of the negative enthalpy duplex stainless steel material is basically the same as that of Example 1, and the only difference is the component ratio.

[0060] Example 4

[0061] This embodiment provides a Fe 62.5 Cr 16.2 Ni 12.5 Mo 3.1 Mn 1.76 C 0.015 Si 0.5 Ti 2.8 Al 0.36 V 0.13 The preparation method of the negative enthalpy duplex stainless steel material is basically the same as that of Example 1, and the only difference is the component ratio.

[0062] Example 5

[0063] This embodiment provides a Fe 62 Cr 16 Ni 12.5 Mo3Mn 1.75 C 0.015 Si 0.5 Ti 3.5 Al 0.4 V 0.16 The preparation method of the negative enthalpy duplex stainless steel material is basically the same as that of Example 1, and the only difference is the component ratio.

[0064] Test results:

[0065] Figure 1 The Fe prepared in Examples 1-5 of the present invention a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j X-ray diffraction patterns of a series of negative enthalpy duplex stainless steel materials, showing the dual-phase structure of austenite (FCC) and ferrite (BCC);

[0066] Figure 2 The Fe prepared in Examples 1-5 of the present invention a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j Room temperature tensile stress-strain curves of a series of negative enthalpy duplex stainless steel materials; the yield strength, tensile strength and uniform elongation of the alloy can be obtained from the figure.

[0067] Figure 3The Fe prepared in Examples 1-4 of the present invention a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j Polarization curves of a series of negative enthalpy duplex stainless steel materials in 3.5wt.% NaCl aqueous solution; the pitting corrosion resistance potential of the alloy can be obtained from the figure (as shown by the dotted line).

[0068] In summary, the present invention provides a negative enthalpy duplex stainless steel material with high strength, high plasticity and high corrosion resistance and a preparation method thereof. a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j A series of negative enthalpy duplex stainless steel materials are composed of iron, chromium, nickel, molybdenum, manganese, carbon, silicon, titanium, aluminum and vanadium in a certain ratio and are made by vacuum arc melting furnace. The structure of this series of negative enthalpy duplex stainless steel materials contains ferrite (α, body-centered cubic structure (BCC)) and austenite (γ, face-centered cubic structure (FCC)), and the alloy microstructure and mechanical properties can be regulated by adjusting the proportion of different metal elements. This series of negative enthalpy duplex stainless steel materials exhibits high strength and high plasticity mechanical properties. At the same time, negative enthalpy duplex stainless steel materials exhibit excellent corrosion resistance.

[0069] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance, characterized in that: The negative enthalpy duplex stainless steel material is Fe a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j ; Wherein: a, b, c, d, e, f, g, h, i and j correspond to the mass percentage ratio of each element, a = 60-70wt%, b = 15-20wt%, c = 10-15wt%, d = 0-5wt%, e = 1-5wt%, f = 0.015wt%, g = 0-1wt%, h = 0-3wt%, i = 0-0.5wt%, j = 0-0.5wt%, d, g, h, i and j are not 0; The negative enthalpy duplex stainless steel material contains ferrite and austenite in structure.

2. The negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance according to claim 1, characterized in that: The negative enthalpy duplex stainless steel material is Fe a Cr b Ni c Mo d Mn e C f Si g Ti h Al i V j ; Wherein: a, b, c, d, e, f, g, h, i and j correspond to the mass percentage ratio of each element, a=62-65wt%, b=16-18wt%, c=12-14wt%, d=2-4wt%, e=1.5-2.5wt%, f=0.015wt%, g=0.45-0.55wt%, h=0.5-3wt%, i=0.1-0.5wt%, j=0.03-0.2wt%.

3. The negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance according to claim 1, characterized in that: The negative enthalpy duplex stainless steel is Fe 64.2 Cr 16.6 Ni 12.8 Mo 3.2 Mn 1.8 C 0.015 Si 0.5 Ti 0.7 Al 0.16 V 0.03 , Fe 63.6 Cr 16.5 Ni 12.7 Mo 3.1 Mn 1.8 C 0.015 Si 0.5 Ti 1.4 Al 0.23 V 0.06 , Fe 63.1 Cr 16.3 Ni 12.7 Mo 3.1 Mn 1.78 C 0.015 Si 0.5 Ti 2.1 Al 0.3 V 0.1 , Fe 62.5 Cr 16.2 Ni 12.5 Mo 3.1 Mn 1.76 C 0.015 Si 0.5 Ti 2.8 Al 0.36 V 0.13 and Fe 62 Cr 16 Ni 12.5 Mo3Mn 1.75 C 0.015 Si 0.5 Ti 3.5 Al 0.4 V 0.16 One of them.

4. The negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance according to claim 1, characterized in that: The purity of each element in the negative enthalpy duplex stainless steel material is Fe≥99.95%, Cr≥99.95%, Ni≥99.95%, Mo≥99.99%, Mn≥99.8%, C≥99.99%, Si≥99.99%, Ti≥99.99%, Al≥99.99% and V≥99.95%.

5. A method for preparing a negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: The raw materials are placed in an arc melting furnace according to the component ratio, and arc is struck to melt the raw materials in an inert atmosphere to obtain the negative enthalpy duplex stainless steel material.

6. The method for preparing the negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance according to claim 5, characterized in that: The preparation method specifically comprises the following steps: firstly, ultrasonically cleaning each raw material; secondly, placing each raw material after cleaning in a water-cooled copper crucible in an arc melting furnace in order of melting point from low to high according to the component ratio; placing titanium sponge at the middle crucible position of the water-cooled copper crucible; and striking an arc to melt the raw materials in an inert atmosphere environment until they are fully miscible to obtain the negative enthalpy duplex stainless steel material.

7. The method for preparing a negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance according to claim 6, characterized in that: The inert atmosphere environment is a vacuum oxygen-free environment, which is obtained by the following operations: using a mechanical pump to evacuate the arc melting furnace to a vacuum degree of <4 Pa, and then using a molecular pump to evacuate the furnace to a vacuum degree of <4×10 -4 Pa, and then introduce argon gas with a purity of 99.99% to 0.08Mpa; repeat the above process twice, and finally fill the argon gas to 0.06Mpa, and then arc melt the sponge titanium twice to absorb residual oxygen.

8. The method for preparing a negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance according to claim 6, characterized in that: In the step of arc-smelting the raw material under an inert atmosphere, the number of arc-smelting of the raw material is greater than 4 times, and after each arc-smelting, the arc-smelted material in the water-cooled copper crucible is turned over before the next arc-smelting, and the sponge titanium is arc-melted before the next arc-smelting.

9. The method for preparing a negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance according to claim 8, characterized in that: The time of each arc melting is 1.0-2.0min, and in addition to the first arc melting and the last arc melting, the arc melting of the raw materials also includes magnetic stirring of the raw materials.

10. The method for preparing the negative enthalpy duplex stainless steel material having high strength, high plasticity and high corrosion resistance according to claim 8, characterized in that: The voltage of each arc melting is 10-15V, and the current of each arc melting is 300-350A.

Citation Information

Patent Citations

  • Low-density high-strength high-plasticity high-entropy alloy material and preparation method thereof

    CN111549270A

  • Iron-rich high-toughness double-phase high-entropy stainless steel and preparation method thereof

    CN115491564A

  • Method for preparing medium-entropy austenitic heat-resistant steel

    CN115976314A

  • High-strength corrosion-resistant double-phase medium-entropy stainless steel and heat treatment method thereof

    CN116904882A

  • Duplex stainless steel pipe

    WO2023054599A1

Cited By

  • Negative mixing enthalpy low-nickel stainless steel material and preparation method thereof

    CN121610717A

  • High-strength, high-plasticity and corrosion-resistant low-cost negative enthalpy stainless steel material and preparation method thereof

    CN122466367A